2021
DOI: 10.3389/fneur.2021.736684
|View full text |Cite
|
Sign up to set email alerts
|

Dependency in Activities of Daily Living During the First Year After Stroke

Abstract: Background: Dependency in personal activities of daily living (ADL) is a common short-term and long-term consequence of stroke and requires targeted rehabilitation. As the duration of hospital stay has become shorter in recent decades, early identification of patients who require rehabilitation has become vital. To our knowledge, no study has investigated whether ADL dependency in the very early stages after admission to the stroke unit can explain ADL dependency 3 and 12 months later. This knowledge would fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 37 publications
0
16
0
1
Order By: Relevance
“…To investigate which biomarkers are related to stroke recovery, the BI scores of 40 patients with stroke upon admission and at the 3-month follow-up appointment were collected. As suggested by previous studies ( 18 , 30 , 31 ), these 40 patients were divided with stroke into two groups: ADL independent with a BI score ≥95 and ADL dependent with a BI score ≤90 using the BI score from the 3-month follow-up appointment. Next, a hierarchically clustered heatmap was constructed to present the lipids that were closely linked to these two groups.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate which biomarkers are related to stroke recovery, the BI scores of 40 patients with stroke upon admission and at the 3-month follow-up appointment were collected. As suggested by previous studies ( 18 , 30 , 31 ), these 40 patients were divided with stroke into two groups: ADL independent with a BI score ≥95 and ADL dependent with a BI score ≤90 using the BI score from the 3-month follow-up appointment. Next, a hierarchically clustered heatmap was constructed to present the lipids that were closely linked to these two groups.…”
Section: Resultsmentioning
confidence: 99%
“…Function-based sessions target ADLs (grooming, self-feeding, toileting, dressing, and/or bathing) or for higher-level patients may simulate instrumental ADLs, such as home management, financial management, medication management, and leisure/work tasks. While performing some of these tasks in the acute care setting can pose a challenge given the environment, research has shown that task-specific training and returning to valued occupations during recovery may be beneficial 16–20 . For example, therapists may have a patient perform grooming tasks by integrating the affected arm at the appropriate level, ranging from a dependent stabilizer to a functional assist.…”
Section: Methodsmentioning
confidence: 99%
“…While performing some of these tasks in the acute care setting can pose a challenge given the environment, research has shown that task-specific training and returning to valued occupations during recovery may be beneficial. [16][17][18][19][20] For example, therapists may have a patient perform grooming tasks by integrating the affected arm at the appropriate level, ranging from a dependent stabilizer to a functional assist. They may set up the sink so that all supplies are in the affected visual field to promote scanning and attention.…”
Section: Occupational Therapy: Evaluation Treatment and Interventionmentioning
confidence: 99%
“…At the same time, respondents with severe and total dependence were 21.2% of each. Based on the study conducted by Wurzinger (2021), the level of dependency on activity daily living at 3 and 12 months is related to the patient's dependency within 36-48 hours after admission to the hospital. Dependency was identified by some factors, including cognitive impairment and older age.…”
Section: Severity Of Stroke Risk Fall Spearman's Rhomentioning
confidence: 99%
“…Dependency in stroke patients mostly affects daily activities. This is a common impact of post-stroke, and it can be persisted in 35% of stroke patients within the first year of stroke (Wurzinger, 2021). The level of dependence of stroke patients can be assessed using the Barthel index scale.…”
Section: Introductionmentioning
confidence: 99%